ANALISIS VARIASI LUASAN HEATSINK TERHADAP UNJUK KERJA MODUL GENERATOR TERMOELEKTRIK (TEG) MEMANFAATKAN PANAS BUANGAN KONDENSOR KULKAS - Wiradika, Yudha; Ilminafik, Nasrul; Junus, Salahuddin; Hardiatama, Intan; Nashrullah, M Dimyati (Jurusan Teknik Mesin, 2024)
Heat energy is generally only used by humans for heating an object and then heat wastefully into the environment without being converted into other energy. This study aims to find out how to utilize waste heat from 6U type refrigerator condensers by using thermoelectric generator modules. This study uses an experimental method that is used to compare the performance of a thermoelectric generator to convert waste heat from a condenser to a variation of 120cm2, 96cm2, and 72cm2 heatsink area. In the study taken every 5 minutes for 2 hours this results in a declining value. The variation of the 120cm2 heatsink area produces a temperature difference of 12.4oC - 9.4oC, the output power is 0.00119 Watts - 0.00072 Watts, and produces an efficiency of 0.014% - 0.011%. In testing the variation of 96cm2 heatsink area, it produces a temperature difference of 8.1oC - 5.3oC, the output power is 0,00055 Watt - 0,00025 Watt, and produces an efficiency of 0,010% - 0,007%. In testing the variation of the 72cm2 heatsink area it produces a temperature difference of 6.9oC - 4.5oC, the output power is 0,00042 Watts - 0,00019 Watts, and produces an efficiency of 0.009% - 0.006%. Of the three variations of the heatsink area that have been tested, the variation of the 120cm2 heatsink area produces the best results compared to other heatsink area variations.